SKEMA PENTASYARUFAN ZAKAT UNTUK PENANGGULANGAN COVID 19: Study Analisi Kritis Fatwa MUI No 23 Tahun 2020 Tentang Pemanfatan Harta Zakat, Infak, Dan Shadaqah Untuk Penanggulangan Wabah Covid-19 Dan Dampaknya - Agus Salim (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2020)
Zakat is one of the obligatory worship with detailed explanation in the Qur’an and Hadits, both about the subject, object, degree of obligation and to whom is given. A few months ago, a Fatwa from the Indonesian Ulema Council (MUI) appeared on the introduction of zakat for the handling of covid-19 victims and their handlers. From this fatwa then negative assumptions are formed, as if the zakat property is not assigned to the existing zakat according to the guidance of the Qur’an and the Hadits. In this paper the author tries to scheming the contents of the fatwa using the methodology of liberry risert, it is hoped that what is stated in the fatwa of the preaching of zakat and shadaqah can be understood by the public well